A study on the optimization method for a multi-body system using the response surface analysis - Jung, Sung-Pil; Park, Tae-Won; Jun, Kab-Jin; Yoon, Ji-Won; Lee, Soo-Ho; Chung, Won-Sun (Journal of mechanical science and technology, 2009)
An optimization method, which minimizes the characteristic value of a system using response surface analysis, is presented. Plackett-Burman design is used as a screening method. Using the response surface analysis, second order recursive model function is estimated as an objective function. To verify the reliability of the model function, an F-test based on the analysis of variances table is used. Lastly, the sequential quadratic-programming method is used to find the value of design parameters. By applying the preceding procedure to a multi-body dynamic model, the optimization process presented in this study is verified.